2014
DOI: 10.1111/bju.12497
|View full text |Cite
|
Sign up to set email alerts
|

Impact of androgen suppression and zoledronic acid on bone mineral density and fractures in the Trans‐Tasman Radiation Oncology Group (TROG) 03.04 Randomised Androgen Deprivation and Radiotherapy (RADAR) randomized controlled trial for locally advanced prostate cancer

Abstract: Objective• To study the influence of adjuvant androgen suppression and bisphosphonates on incident vertebral and non-spinal fracture rates and bone mineral density (BMD) in men with locally advanced prostate cancer. Patients and Methods• Between 2003 and 2007, 1071 men with locally advanced prostate cancer were randomly allocated, using a 2 × 2 trial design, to 6 months i.m. leuprorelin (androgen suppression [AS]) before radiotherapy alone ± 12 months additional leuprorelin ± 18 months zoledronic acid (ZdA), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…They found that compared with baseline DEXA measurements, BMD at the hip measured at 4 years was reduced with both 6 and 18 months of ADT (1.7% and 3.7%, respectively; p < 0.01) and this BMD reduction was prevented by concomitant administration of zoledronate. There was however, no significant difference in the primary endpoint of incidence of vertebral fractures seen although this was attributed to insufficient sample size and duration of follow-up [86]. Their results however confirmed those from several prior smaller studies [72][73][74]77] that all demonstrated a benefit with bisphosphonates in reducing BMD loss among prostate cancer patients on ADT.…”
Section: Bisphosphonatessupporting
confidence: 57%
“…They found that compared with baseline DEXA measurements, BMD at the hip measured at 4 years was reduced with both 6 and 18 months of ADT (1.7% and 3.7%, respectively; p < 0.01) and this BMD reduction was prevented by concomitant administration of zoledronate. There was however, no significant difference in the primary endpoint of incidence of vertebral fractures seen although this was attributed to insufficient sample size and duration of follow-up [86]. Their results however confirmed those from several prior smaller studies [72][73][74]77] that all demonstrated a benefit with bisphosphonates in reducing BMD loss among prostate cancer patients on ADT.…”
Section: Bisphosphonatessupporting
confidence: 57%
“…Furthermore, men who were previously treated with bisphosphonates appeared to benefit more from the EX intervention than men who were not treated with bisphosphonates. Bisphosphonates are a class of drugs that prevent loss of bone mass, and in survivors of prostate cancer they may prevent ADT‐induced losses in bone mineral density . Differences in effects could not be explained by session attendance, but perhaps men who were treated with bisphosphonates were more able to comply with the prescribed exercise intensities and consequently had better HRQoL outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Two randomized studies in patients with prostate cancer with no systemic metastases using zoledronic acid failed to show improvement of bone-metastases-free survival 128130 . By contrast, patients with castrate-resistant prostate cancer who were given denosumab showed improvement of bone-metastasis-free survival from a median of 25.2 months on placebo to a median of 29.5 months on denosumab without any difference in overall survival 131 .…”
Section: Managing Skeletal Complications Of Cancermentioning
confidence: 99%